Oxford handbook of pre-hospital care - Greaves, Ian; Porter, Keith M. (Oxford : Oxford University Press, 2020)
This handbook is the invaluable guide to providing high-quality care in a pre-hospital environment. Evidence-based and reflecting new developments in regulation and practice, this second edition is designed to provide key information for all immediate care practitioners, including doctors, paramedics, emergency medical technicians, and community responders. The text has been cross-referenced with the Joint Royal Colleges Ambulance Liaison Committee (JRCALC) handbook and appropriate national clinical guidelines to ensure full clinical relevance.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 18, 2020).
Keywords: Emergency medicine; Disaster medicine